Black and White Hardcore and Middleclass Subjective Cultures A Cross-Validation. Illinois Studies of the Economically Disadvantaged, Technical Report Number 14 - Triandis, Harry C.; Illinois Univ., Urbana. Dept. of Psychology ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The research reported in this document was concerned with determining differences in subjective culture that might be associated with race, sex, social class, and age, and to cross-validate the findings of the previous four reports. Interviewers of the same race and sex as the persons studied were trained for approximately 18 hours using standard procedures, before going into the field. A factorial design was used to generate the types of people sampled. The design consisted of Race (black and white); Social Class (hardcore, working class, middle class), Sex, and Age (18 to 25, or 35 to 45 years old). Ten individuals were studied in each of the 24 cells generated by this design. The hardcore were defined as persons having few skills and little education, who in the opinion of the interviewer could work, but who report that they have not had a job for a year, although they tried to get one. The judgments required were presented in questionnaire form. The 240 persons were asked to make 128 judgments concerning the characteristics of categories of persons; 105 concerning their behavioral intentions toward such persons; 120 judgments concerning their role perceptions; 40 judgments concerning their job perceptions; 90 concerning the antecedent of certain events, and 90 judgments concerning the consequents of these events. (Author/JM)
Sponsoring Agency: Social and Rehabilitation Service (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Age Differences; Blacks; Cultural Differences; Employees; Racial Attitudes; Racial Differences; Role Perception; Sex Differences; Social Attitudes; Social Class; Social Differences; Stereotypes; Unemployment; Whites; Work Attitudes